CYCLODEXTRIN AS SOLUBILIZER AND TARGETING AGENT FOR DRUGS - SINGH, ADITYA NARAYAN; BAGHEL, DILEEP SINGH; KUMAR, BIMLESH; PANDEY, NARENDRA KUMAR; SINGH, SAURABH; SUDHAKAR, KALVATALA; CHARYULU, R. NARAYANA (International Journal of Applied Pharmaceutics, 2024)
Natural cyclic oligosaccharides called cyclodextrins (CDs) improve the bioavailability of drugs by the formation of inclusion complexes involving small and macromolecules of poorly soluble compounds in water. CDs act as a solubilizer and targeting agent for drugs with low water solubility, enabling them to effectively target specific cells. Where poorly water-soluble compounds interact with the hydrophobic cavity of CDs to enhance their solubility. CDs are effective drug delivery agents because of their essential function as processing complex carriers. Various ligands can be utilized to modify the surface of cyclodextrin to actively target drugs. It is possible to consider it to have amphiphilic characteristics by enduring a chemical transformation with long aliphatic chains, and a variety of amphiphilic CDs can produce nanoparticles without the usage of surfactants. CD-nanocarriersact as cargo with solubilizers for drugs and a targeting agent for specific receptors present in specific cells and release the drug. CDs have many applications, including the reduction of drug-induced gastrointestinal discomfort, avoiding interactions between drug-drug and drug-excipient, and transforming drug products that are liquid into microcrystalline solid powders. Because of their biocompatibility and biodegradability, CDs have outstanding properties that make them particularly useful in the pharmaceutical and cosmetic industries.